EXTH-59. GENERATION OF A THIRD GENERATION CAR T CELL THAT SIMULTANEOUSLY TARGETS WILDTYPE EGFR AND ITS MUTANT ISOFORM EGFRVIII FOR TREATMENT OF GLIOBLASTOMA. (12th November 2021) - Wilkinson, Daniel; Ryan, Katherine; Chandramohan, Vidyalakshmi; Landi, Daniel; Bigner, Darell; Fecci, Peter
Abstract: Glioblastoma (GBM) is the most aggressive primary brain cancer with a median survival of less than 16 months. This dire prognosis signifies the urgent need for improved treatment options, such as immunotherapy. Chimeric antigen receptor (CAR) T cells have helped revolutionize immunotherapy, achieving considerable success in eliminating hematological cancers but generally failing to control solid tumors. One major hindrance to CAR T cell success in solid tumors is tumor heterogeneity. Tumor-associated or tumor-specific antigens (TAA or TSA, respectively) are rarely expressed by all malignant cells within a tumor. As a specific example in GBM, the most prevalent TSA, EGFRvIII, is present in just 30% of tumors, and then on only 30-50% of cells. Our pre-clinical and clinical experiences with CAR T cells reveal that tumors possessing as few as 5-10% EGFRvIII-negative cells will easily escape EGFRvIII-targeted CARs. Tumor cells that lack EGFRvIII expression often overexpress the wildtype isoform of EGFR (EGFRwt). Notably, EGFR is absent on normal brain. Therefore, a superior approach would be to simultaneously target EGFRvIII and EGFRwt, an approach that would bypass EGFR heterogeneity in EGFRwt/EGFRvIII-expressing tumors. Here, we generated a third generation CAR using the D2C7 single-chain variable fragment (scFv) targeting moiety that recognizes an epitope present in EGFRwt and EGFRvIII. Initial in vitro characterization of D2C7 CAR validated the specificity and function of D2C7 CAR, as it potently killed murine cell lines engineered to express either EGFRwt or EGFRvIII, but not a cell line expressing neither. Concomitant IFN-γ release supported these conclusions. Additionally, D2C7 CAR killed the human-derived GBM cell line U87 and vIII-transfected U87, U87vIII. Importantly, intracranially-administered D2C7 CAR significantly prolonged survival of mice bearing orthotopic U87vIII or U87/U87vIII heterogeneous tumors compared to mock-treated controls. Altogether, these data provide evidence that D2C7 CAR T cells represent a viable therapeutic option for EGFRwt/EGFRvIII heterogeneous tumors.